Scoring athletic performances for age groups - Grammaticos, B. (New Studies in Athletics, 2009)
Current scoring tables for athletics events, including the IAAF Tables for Combined Events, do not take in account the age of the athlete. This creates problems for evaluating the performance of athletes who, because of their age, have not yet reached or are past their full physical capacities. With the growing numbers of young and masters category athletes in the sport, this issue is of increasing interest. This article addresses the issue of scoring for masters athletes with an approach based on physical modelling. Following on from an article published in NSA in 2007, the author, a physicist working in the modelling of biological phenomena, analyses physiological data using a "toy" model of athletic performance. He then analyses the dependence of performance on age for various disciplines. By introducing a number of simple assumptions he is able to explain the age factors used for computing the equivalent performances of masters category athletes. He then shows how these can be used directly in a scoring model and proposes a consistent approach for scoring the performanc of masters athletes. Although scoring for younger athletes is discussed, the lack of available data prevented the development of an equivalent model at this time.